Employee Job Satisfaction Mediates the Effect of Teamwork and Work Discipline on Employee Performance - Nahan, Goza Ralinsa; Fushen (Journal of Humanities, Social Science, Public Administration and Management (HUSOCPUMENT), 2025)
Human Resources (HR) have an important influence on the success of an organization. To find out the results of employee performance, employee performance is assessed using indicators in the form of quantity and quality of employees in carrying out tasks according to their responsibilities. Teamwork and employee discipline can affect the results of employee performance. In addition, employee job satisfaction is also expected to be an important role in strengthening the relationship between teamwork and employee discipline in improving employee performance. This study is descriptive associative, so it is only limited to revealing facts that explain the causality between variables with proof of hypotheses and quantitative data processing. The sample of this study was taken from the entire population of 107 respondents. Data were obtained through questionnaires. The analysis technique used to test the hypothesis used the Structural Equation Model (SEM) model through the Partial Least Square (PLS) approach. In this study, seven hypotheses were tested and the researchers found that teamwork did not have a significant effect on employee performance, but with high job satisfaction, it could increase teamwork so that it could improve employee performance. This shows that although teamwork does not always have a significant effect on employee performance, the existence of job satisfaction as a mediating variable can strengthen the relationship. In other words, although good teamwork does not directly affect employee performance, increased job satisfaction resulting from solid teamwork can improve employee performance. Employees who are satisfied with the working relationships within their team tend to be more motivated to contribute better, increase productivity, and provide quality service.